Docking studies reveal zerumbone targets β-catenin of the Wnt-β-catenin pathway in breast cancer - Fatima, Ayesha; Abdul, Bustamam; Abdullah, Rasedee; Karjiban, Roghayeh; Lee, Vannajan Sanghiran (Serbian Chemical Society, 2018)
Breast cancer is the second most common cancer among women worldwide.The Wnt-ß-catenin pathway appears to be deregulated in most cancer cells including breast cancer.The role of zerumbone, the active sesquiterpene from Zingiber zerumbet Roscoe, on the Wnt-ß-catenin pathway is relatively unknown, especially detailed molecular studies have yet to be published. Using the Chemistry at HARvard Macromolecular Mechanics (CHARMm) force field-based docking protocol, CDOCKER, the molecular interactions between zerumbone and key proteins of the Wnt-ß-catenin pathway were evaluated in this study.The results suggest that zerumbone has a strong affinity for free ß-catenin in the cytoplasm, as well as the ß-catenin-transcription factor 4 complex in the nucleus.The overall hydrophobic nature of zerumbone allowed its interaction with other hydrophobic residues, such as Trp383, while its active a,ß-unsaturated carbonyl facilitated its interaction with positively charged residues, such as Lys345, Arg386 and Asn415 in the ß-catenin binding pocket. However, the Wnt protein and its frizzled receptor showed no attraction to zerumbone.